2014
DOI: 10.3922/j.psns.2014.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of affective valence on a mixed Spatial Correspondence Task: A reply to Proctor (2013).

Abstract: The present study investigated the influence of emotional valence on the spatial stimulus-key location correspondence effect in three experiments using the Affective Spatial Correspondence task (AffSCt). We initially reanalyzed the results of Conde et al. (2011) according to the model proposed by Proctor (2013). In that study, compatible and incompatible responses were chosen according to the participants' team preference. In one block, the volunteers had to press a key on the same side for the Favorite team a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
11
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 21 publications
6
11
0
11
Order By: Relevance
“…The present results are consistent with Conde et al's (2011) finding as well as reinterpretation of the finding (also see Conde et al, 2014). When analysed in terms of stimulus valence, there was a standard SRC effect for positive stimuli, but the effect was reversed for negative stimuli.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present results are consistent with Conde et al's (2011) finding as well as reinterpretation of the finding (also see Conde et al, 2014). When analysed in terms of stimulus valence, there was a standard SRC effect for positive stimuli, but the effect was reversed for negative stimuli.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, positive stimuli facilitated retrieval of compatible mapping, whereas negative stimuli facilitated retrieval of incompatible mapping. Although Conde et al (2014) have already agreed with this interpretation, the present experiment provides the first empirical evidence that directly supported the interpretation.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…He showed that, when Favorite stimuli signaled compatible and Rival the incompatible mapping-rule, the MRTs are shorter than in the opposite situation. Conde et al (2014) replicated these results and showed that the emotional effect vanished when neutral soccer stimuli (fake soccer team) were used. The results described in the current paper showed different patterns of temporal distribution for each affective valence (favorite and rival stimuli), even sharing the fact that compatible and incompatible practices were made in different blocks of trials.…”
Section: Discussionsupporting
confidence: 72%